TINJAUAN YURIDIS ATAS TINDAKAN DEBITUR YANG MENOLAK PENGOSONGAN BARANG JAMINAN YANG DIEKSEKUSI OLEH BANK - YOICE IRENE LAMTIUR P (PREMISE LAW JURNAL, 2015)
In a banking credit, the bank as creditor usually do the collateral binding in which in this research is a commitment right to save the credit distribution according to UUHT No. 4 of 1996. If debtor is in default, the creditor has a right on execution of the quarantee object based on the applied rule. This research is a normative low study in descriptive analytic design. Based on the result of research it indicates that the procedure of execution of quarantee object is if the debtor is in default in payment the debt that indicated by the warning letter by creditor for 3 times and somation of the legal representative of creditor for 3 times. The implementation of the execution of the guarantee object gain the opposed of debtir so the creditor to the enforcement by flat execution from the district court of Batam by ask the bailiff of the court of Batam and the police of Batam. The creditor before the execution must do the negotiation to the creditor to avoid the resistance in the execution of the object